Dasatinib in First- and Second-Line Therapy of Chronic Myeloid Leukemia: Efficacy, Safety and Quality of Life - TI Ionova; NB Bulieva; OYu Vinogradova; TA Gritsenko; LK Kozlova; GB Kuchma; EG Lomaia; ER Machyulaitene; TP Nikitina; NV Novitskaya; AYu Rodionova; EI Usacheva; et al. (Клиническая онкогематология)
Background & Aims. The article presents results of two observational, prospective, multicenter studies “Quality of Life, Symptom Profile, and Adherence to Treatment in Adult Patients with Newly Diagnosed Chronic Phase Chronic Myeloid Leukemia Receiving Dasatinib” (2012–2015) and “Quality of Life and Symptom Profile in Imatinib-Resistant or Intolerant Patients with Chronic Myeloid Leukemia” (2011–2014).